Crisis Management - Hashim, A. H. (2014)
Unplanned events can have a devastating effect on businesses.Crises such as fire, damage to stock, illness of key staff or IT system failure could all make it difficult or even impossible to carry out our normal day-to-day activities. At worst, this could see us losing customers and irreparable damage to UNIMAS reputation.But with good management, we can take steps to minimize the potential impact of a disaster - and ideally prevent it happening in the first place.The lecture focuses on understanding what is a crisis, the crisis phases and remedial actions.